Contribuição da deposição atomosférica seca de compostos nitrogenados na disponibilização de nutrientes e na indução do fenômeno de eutrofização em reservatório localizado no interior do estado de São Paulo - Garcia, Gabriel [UNESP] (2013)
During the last few years, the maintenance of conditions suitable for life on the planet has been placed under threat of a series of phenomena of environmental imbalance, induced or enhanced by anthropogenic activities. Most of them originate from the excess nitrogen in the environment, a condition strongly linked to the structural bases of mankind subsistence: food and energy production. The understanding of this multifaceted relationship between human livelihoods and environmental imbalances is the prime requirement for success in the most pressing issues in the preservation of the Earth's ecosystem. Thus, this research was based on the relationship between nitrogen, biosphere and environment, and sought to contribute to the advancement of knowledge about the impacts of human action in this relationship, specifically with regard to the role of the atmosphere dispersion and availability of nitrogen to aquatic ecosystems. The study aimed at evaluating quantitatively the contribution of dry atmospheric deposition on total intake of soluble chemical species of nutrients, especially nitrogen compounds, into a reservoir and evaluate its potential to induce the phenomenon of eutrophication of this ecosystem, located in the countryside of the State of São Paulo, in Araraquara city region, under the influence of climatic and agricultural peculiar to the region. Initially, were identified the main (or most significant) sources of nutrients to the reservoir and then established a conceptual model of nutrient fluxes to the ecosystem studied, from which were based all experimental approaches and results interpretations. The availability of the macronutrients nitrogen and sulfur to the water column's main sources, in descending order, the entry of water from the reservoir by Anhumas, the dry atmospheric deposition, and finally, the sediment of the water body. In this balance, the role of the atmosphere (by dry deposition) was also relevant...